Influence of different sample preparation techniques on imaging viruses and virus-like particles by scanning electron and scanning transmission electron microscopes - Kąkol, Monika; Tagliasacchi, Ezher; Borkowski, Andrzej; Słowakiewicz, Mirosław (Frontiers in Microbiology, 2023)
Scanning electron microscopy (SEM) and scanning transmission electron microscopy (STEM) were applied as many laboratories to visualise and image viruses and virus-like particles (VLPs). Two bacteriophages, P1 and Φ6, were chosen as model microorganisms known for their distinct structure and viruses obtained from biofilms associated with modern travertines (Terme di Saturnia, Italy; Karahayıt ‘Kızılsu’ and Pamukkale, Turkey) were also investigated. Three protocols, 1) full, 2) simplified and 3) all at once were developed and tested for sample preparation and imaging. The full procedure enabled the observation of P1 bacteriophages whereas the simplified protocol, while successful in visualizing Φ6, did not yield satisfactory results for P1. The preservation state of the latter appeared to be compromised and led to less informative images in SEM and STEM. Viruses in biofilms exhibited various levels of mineralization and aggregation, complicating their characterization. In the all at once procedure, although effective in preserving bacteriophage tails, excessive coating and thickening of samples with heavy chemical reagents, led to a reduction in overall image quality. Despite a final washing step, some residues of chemical reagents (OsO4 and uranyl acetate) remained, impacting the clarity of the images. Finally, the results obtained emphasize the critical role of sample preparation and imaging techniques in effectively visualizing and characterizing viruses and VLPs. The choice of analytical procedure significantly influences the resolution and preservation state of the observed bacteriophages and VLPs. It is suggested that the appropriate imaging technique is carefully selected based on the specific objectives of the project and the nature of samples being investigated to obtain the best images of the viruses.